COMPARATVE STUDY OF WORK LIFE BALANCE AMONG PRIVATE AND PUBLIC SECTOR BANKING EMPLOYEES IN PERAMBALUR DISTRICTBanking industry is an emerging industry in India, the entry of private sector and foreign banks have brought various essential changes in the ba - GEETHA, S.GEETHA; Rajendran, Dr R. (IJRDO - Journal of Applied Management Science, 2017)
Banking industry is an emerging industry in India, the entry of private sector and foreign banks have brought various essential changes in the banking industry. The menace of work- life imbalance is noticeable in banking industry. Employees in the banks take painful effort to deliver the various needs of its customers. Work deadlines are getting compact and the individual’s jobs are loaded and added with quality output. Due to work in pressure, it becomes hard to maintain balance between professional and family life. The output of the banking sector is dependent on the quality of human resources. The basic function of human resource development is to facilitate performance improvement, measured in terms of finance indicators of operational efficiency and quality of financial services provided. The twin challenges faced by the banks’ managements are that of retaining the prevailing employees and providing a satisfying work environment for all employees. The study attempts to find out the issues related with managing professional and personal life of employees in banking industry. The major objective of this paper is to identify specific issues and challenges in work life balance in banking industry and to suggest measures to improve work life balance.